Younger age at colorectal cancer diagnosis in hereditary gastrointestinal cancer predisposition syndromes and Lynch syndrome: a nationwide analysis - Eldesouki, Mohamed H.; Ibrahim, Ahmed; Katona, Bryson W.; Burke, Carol; Shaukat, Aasma (Journal of Gastrointestinal Oncology; Vol 17, No 3 (June 29, 2026): Journal of Gastrointestinal Oncology, 2026)
Background: Many hereditary gastrointestinal cancer predisposition syndromes (HGCPS), including Lynch syndrome (LS), increase the risk for colorectal cancer (CRC). Sporadic CRC in average-risk individuals has shifted toward younger ages; however, the same trend in patients with HGCPS/LS remains underexplored. We aimed to evaluate temporal trends in age at CRC diagnosis among patients with HGCPS/LS compared with a non-hereditary/average risk cohort in a large national database.Methods: We used the TriNetX database to identify patients with HGCPS/LS from 2010 to 2024. We compared age at CRC diagnosis between patients with HGCPS/LS and a non-hereditary/average risk cohort.Results: Among 136,394 patients with HGCPS/LS, 6,561 (4.8%) were diagnosed with CRC, compared with 364,189 (0.34%) in the average risk cohort. The peak age at CRC diagnosis shifted earlier by 10 years, from 45–54 years in 2010–2017 to 35–44 years in 2018–2024, and the proportion diagnosed before age 45 rose from 35% to 51%. Among HGCPS/LS patients, the mean age at CRC diagnosis declined from 51±17 to 47±18 years; during 2018–2024 it was 47±18 years vs. 58±14 years in the average risk cohort. Overall, 55.4% of HGCPS/LS cases occurred by age 49 vs. 13.8% of controls, and HGCPS/LS patients were diagnosed at a median age 20.0 years younger (P